Ab initio-MO Study of Route-Map to Biosynthesis of Bicyclomonoterpenes - Taherkhani, Mahboubeh (Asian Journal of Chemistry, 2011)
The biogeneses of cyclic terpenes are usually assumed to involve classical and non-classical carbocation intermediates resulting from dissociation of the geranylpyrophosphate 1. Formation of carbocations and consequent rearrangements and formation of stereoisomers, explain the cyclization to several cyclic monoterpenes. To study the route map of biosynthesis as well as synthesis of bicycle-monoterpenes from geranylpyrophosphate 1, possible intermediates and bicycle-products were designed. Afterwards ab initio calculations were carried out at HF/6- 31G** level of theory using Gaussian software. The results indicated that among cyclic carbocations, classical carbocation 7 was the most stable isomer. However the non-classical carbocation 5 was the least stable one. In regard with studied bicyclo-monoterpenes, 24 was more unstable (21.36 kcal/mol) than 26. The results indicated that among products, the fenchane 26 was the most stable isomer; however the pynene type 24 was the least stable one. The results indicated that kinetic considerations control the outcome of reaction and thermodynamic rules have less roll in route map of biosynthesis.